Грамматическая субстантивная омография в русском языке - Jerzy Kaliszan (Studia Rossica Posnaniensia)
This article is devoted to characterizing one of the main areas of contemporary Russian stress homography (i.e. the relationship between words that are spelled in the same way but pronounced differently as a result of different word stress). The author’s aim is to attempt to describe all kinds of grammatical (paradigmatical) substantival homography that manifests itself in correlations between inflectional forms of the same lexeme such as учителя – учителя, письма – письма, (по) снегу – (на) снегу, etc.